Establishment of the Indicator System for Livable Cities Based on Sustainable Development Goals and Empirical Research in China - Maomao Yan; Feng Yang; Jiaqi Shi; Chao Li (Land)
Against the backdrop of increasing urban population and continuous expansion of urban scales, achieving “people-centered” urban sustainable development, namely building livable and sustainable cities, faces formidable challenges. Under the shared global vision of achieving the 2030 Sustainable Development Goals (SDGs), existing research has rarely explored the alignment between the construction of livable cities and the SDGs. This study constructs a scientific and universally applicable evaluation system for urban livability to clarify that building livable cities is a crucial pathway to promoting urban sustainable development. This study integrates the core principles of the three pillars of the United Nations’ sustainable development, the five-dimensional classification logic of the Global Urban Monitoring Framework, and the performance evaluation key points of ISO/TC 268 standards for SC1 “smart community infrastructure” to construct a six-dimensional livable city evaluation system covering society, economy, culture, environment, governance, and infrastructure. Starting from theoretical research on the connotation of livable cities and their alignment with the SDGs, and based on the research team’s evaluation experience and assessment paradigm of SDGs progress at the urban level, this study uses the “Indicator Library for Cities’ Sustainable Development (ILCSD)” as a technical tool to explore the technical methods for establishing an evaluation index system for livable cities. Meanwhile, combining qualitative research and statistical analysis with China’s development strategic needs, it selects 24 sample cities to analyze the level differences among different types of cities under the proposed index system and to identify the key factors and mechanisms influencing the sustainable development of livable cities. Through theoretical research and empirical analysis, this study has derived a set of evaluation indicators for livable cities oriented towards the SDGs, offering urban management stakeholders a reasonable and comprehensive universal evaluation technical tool to enhance urban livability and promote the implementation of the SDGs.